# Thread: Finding Taylor series for f

1. ## Finding Taylor series for f

Hello there, I was having some trouble with this problem:

Find the Taylor series for f centered at 4 if:

$\displaystyle $f^n(0) = \frac{(-1)^nn!}{3^n(n+1)}$$

What is the radius of convergence of the Taylor series?

Help appreciates.

2. ## Re: Finding Taylor series for f

Originally Posted by Intrusion
Hello there, I was having some trouble with this problem:

Find the Taylor series for f centered at 4 if:

$\displaystyle $f^n(0) = \frac{(-1)^nn!}{3^n(n+1)}$$

What is the radius of convergence of the Taylor series?

Help appreciates.
To find the Taylor series for f centered at 4, you need the values of $\displaystyle f^n(4)$.

3. ## Re: Finding Taylor series for f

Originally Posted by Intrusion
Hello there, I was having some trouble with this problem:

Find the Taylor series for f centered at 4 if:

$\displaystyle $f^n(0) = \frac{(-1)^nn!}{3^n(n+1)}$$

What is the radius of convergence of the Taylor series?

Help appreciates.
The Taylor expansion of f(*) around z=0 is...

$\displaystyle f(z)= \sum_{n=0}^{\infty} \frac{(-1)^{n}\ z^{n}}{3^{n}\ (n+1)}$ (1)

... and the series (1) has radius of convergence 3 because the singularity of the function in z=-3. Therefore the series of f(*) centered in z=4 has radius of convergence 7...

Kind regards

$\displaystyle \chi$ $\displaystyle \sigma$

4. ## Re: Finding Taylor series for f

The problem is ill defined, we have no sufficient information about $\displaystyle f$ . For example

$\displaystyle f(x)=\begin{Bmatrix} \displaystyle \sum_{n=0}^{\infty}\dfrac{(-1)^n}{3^n(n+1)}x^n& \mbox{if}& |x|<3\\x-4 & \mbox{if}& |x|\geq 3\end{matrix}\quad g(x)=\begin{Bmatrix} \displaystyle \sum_{n=0}^{\infty}\dfrac{(-1)^n}{3^n(n+1)}x^n& \mbox{if}& |x|<3\\|x-4| & \mbox{if}& |x|\geq 3\end{matrix}$

We have $\displaystyle f^{(n)}(0)=g^{(n)}(0)=\dfrac{(-1)^nn!}{3^n(n+1)}$ . However: a) The Taylor series of $\displaystyle f$ centered at $\displaystyle 4$ has radius of convergence $\displaystyle +\infty$ . b) The Taylor series of $\displaystyle g$ centered at $\displaystyle 4$ does not exist .

5. ## Re: Finding Taylor series for f

Originally Posted by chisigma
The Taylor expansion of f(*) around z=0 is...

$\displaystyle f(z)= \sum_{n=0}^{\infty} \frac{(-1)^{n}\ z^{n}}{3^{n}\ (n+1)}$ (1)

... and the series (1) has radius of convergence 3 because the singularity of the function in z=-3. Therefore the series of f(*) centered in z=4 has radius of convergence 7...
May be that a further explanation from me is necessary... if we consider the series expansion...

$\displaystyle g(x)= \sum_{n=0}^{\infty} \frac{(-1)^{n}\ x^{n}}{3^{n}}= \frac{1}{1+\frac{x}{3}}$ (1)

...it is not too difficult to obtain...

$\displaystyle f(x)= \sum_{n=0}^{\infty} \frac{(-1)^{n}\ x^{n}}{3^{n}\ (n+1)}= \frac{1}{x}\ \int_{0}^{x} g(\xi)\ \d \xi = \frac{3\ \ln (1+\frac{x}{3})}{x}$ (2)

Now the f(*) defined in (2) is analytic for $\displaystyle x>-3$ and that means that its series expansion centered in $\displaystyle x_{0}>-3$ has radius of convergence $\displaystyle x_{0}+3$ ...

Kind regards

$\displaystyle \chi$ $\displaystyle \sigma$

6. ## Re: Finding Taylor series for f

Originally Posted by chisigma
May be that a further explanation from me is necessary...
Well, independently of your explanation I would insist that the only solution to the problem is: The radius of convergence of the Taylor series for $\displaystyle f$ centered at $\displaystyle x_0=4$ (if exists) can be any $\displaystyle \rho\in[0,+\infty]$ depending on the expression of $\displaystyle f^{(n)}(4)$ .